2010
DOI: 10.1371/journal.pone.0015825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuraminidases from the Highly Pathogenic Avian H5N1 and 2009 Pandemic H1N1 Influenza A Viruses

Abstract: To study the precise role of the neuraminidase (NA), and its stalk region in particular, in the assembly, release, and entry of influenza virus, we deleted the 20-aa stalk segment from 2009 pandemic H1N1 NA (09N1) and inserted this segment, now designated 09s60, into the stalk region of a highly pathogenic avian influenza (HPAI) virus H5N1 NA (AH N1). The biological characterization of these wild-type and mutant NAs was analyzed by pseudotyped particles (pseudoparticles) system. Compared with the wild-type AH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The NA VLPs were spheroidal and approximately 50–200 µm in diameter, similar in morphology to influenza virions (Figure 1) and similar to a previous published full characterization of VLPs expressing only NA and M (Lai et al, 2010). When standardized by the amount of protein, the activity of CA/09 NA VLPs was about 2-fold higher than VN/1203 NA VLPs for both the small NA-XTD substrate (1704 and 879 mU/mg protein, respectively), as well as for the larger fetuin substrate (576 and 341 mU/mg protein, respectively), consistent with previously reported higher NA enzymatic activities of H1N1pdm09 viruses as compared with highly pathogenic H5N1 viruses (Lin et al, 2009; Wu et al, 2010). NA proteins are inherently unstable, and may be even less stable when originating from H5N1 viruses because several potential glycosylation sites and a cysteine that are likely to contribute to tetrameric stability are deleted in the short-stalk NA of HPAI H5N1 viruses (Air, 2011; Blok and Air, 1982).…”
Section: Resultssupporting
confidence: 90%
“…The NA VLPs were spheroidal and approximately 50–200 µm in diameter, similar in morphology to influenza virions (Figure 1) and similar to a previous published full characterization of VLPs expressing only NA and M (Lai et al, 2010). When standardized by the amount of protein, the activity of CA/09 NA VLPs was about 2-fold higher than VN/1203 NA VLPs for both the small NA-XTD substrate (1704 and 879 mU/mg protein, respectively), as well as for the larger fetuin substrate (576 and 341 mU/mg protein, respectively), consistent with previously reported higher NA enzymatic activities of H1N1pdm09 viruses as compared with highly pathogenic H5N1 viruses (Lin et al, 2009; Wu et al, 2010). NA proteins are inherently unstable, and may be even less stable when originating from H5N1 viruses because several potential glycosylation sites and a cysteine that are likely to contribute to tetrameric stability are deleted in the short-stalk NA of HPAI H5N1 viruses (Air, 2011; Blok and Air, 1982).…”
Section: Resultssupporting
confidence: 90%
“…Each NA monomer consists of six identical ␤ sheets (␤) plus several strands (S) and loops (L). Influenza NA enzyme catalytic sites are located at the upper corners of each monomer (tetrameric structure); amino acids encircling active catalytic sites are highly conserved among various influenza A and B virus strains (11,33) NI antibodies are important for NA-based vaccine development. Other researchers have reported that NI antibodies induced by pH1N1 immunizations are cross-reactive with H5N1 viruses in mice (34) and ferrets (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Among these new technologies, the cells culture‐based manufacturing vaccine offers some significant advantages. In several recent publications, it has described selection of highly productive vaccine strain in Vero cells [Wu et al, ; Zhang et al, ].…”
Section: Discussionmentioning
confidence: 99%